(untitled) (Orfeu, 2026)
This article examines Choral Nº 2 by the Goiás composer Estercio Marquez Cunha through the lens of Claude Zilberberg’s tensive semiotics, aiming to understand how specific musical gestures generate effects of meaning related to memory, territory, and affective experience within the context of contemporary choral music in Goiás. Although Goiás’ choral production has been addressed in historical, pedagogical, and institutional studies, analytical approaches that treat the musical work as a field of investigation of the sensible, particularly in dialogue with listening and performance, remain scarce. In this perspective, the present analysis is not conceived as an end in itself, but as a mediating tool between composition, interpretation, and perceptual experience, considering the score as a living poetic-musical text in which sonic and symbolic dimensions are intertwined. After a panoramic examination of the composition, the analysis unfolds across three complementary levels: (1) tensive directions, (2) aspectual modulations, and (3) perceptible operations, revealing the work’s sensible trajectory. The study identifies a tensive path marked by slowness, silence, and harmonic density, which evokes affective landscapes, ancestry, and collective memory, thereby reactivating Goiás’ cultural imaginary. By highlighting the articulation between the plane of expression and the plane of content, the article demonstrates how the work configures a cântico da terra, in which Goiás’ choral tradition is reaffirmed as a sensible event and consolidated as an intangible cultural asset.